(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
Upstream the Cold Chain is a film and an installation of objects produced in the process of producing the film. It is also an experiment in improving access to vaccines and creating hospitable artistic interventions in public health contexts across borders. Presented in the context of <Immune Nations>, Upstream the Cold Chain was first shown in Trondheim, Norway, as part of the 2017 GLOBVAC conference on global health and then later at UNAIDS on the occasion of the World Health Organization’s 70th World Health Assembly in Geneva, Switzerland.